2021
DOI: 10.3390/jcm10245912
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors for the Prevention of Post-Stroke Depression: A Systematic Review and Meta-Analysis

Abstract: There are controversial data on the efficacy and safety profile of selective serotonin reuptake inhibitors (SSRIs) to prevent post-stroke depression (PSD). We performed a systematic search in MEDLINE and SCOPUS databases to identify randomized-controlled trials questioning the use of early SSRI therapy in the post-stroke population and its effect on PSD incidence. We included 6 studies with 6560 participants. We extracted the data on PSD occurrence in association with the treatment arm (SSRI versus placebo), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Thus, albeit the recognition of this new evidence suggests that off-label use of ADT can be expected to decrease, it might yet have contributed to the overtreatment in our sample. At the same time, the early use of SSRI could play a role in PSD prevention, as shown in a recent metaanalysis [13]. The authors found that early SSRI therapy significantly lowers PSD incidence (prevention) but to the disadvantage of increased risk of bone fractures and nausea.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, albeit the recognition of this new evidence suggests that off-label use of ADT can be expected to decrease, it might yet have contributed to the overtreatment in our sample. At the same time, the early use of SSRI could play a role in PSD prevention, as shown in a recent metaanalysis [13]. The authors found that early SSRI therapy significantly lowers PSD incidence (prevention) but to the disadvantage of increased risk of bone fractures and nausea.…”
Section: Discussionmentioning
confidence: 88%
“…Previous evidence of clinical trials suggests that antidepressant treatment (ADT)-especially selective serotonin reuptake inhibitors (SSRI)-can be an effective agent to treat PSD or lower the risk to develop depressive symptoms after stroke [9][10][11][12][13]. Although treatment guidelines concordantly emphasize the need of early identification followed by swift and evidence-based treatment of PSD [14][15][16], PSD still remains underdiagnosed and undertreated [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence underlined the need for early identification of PSD risk factors, which represents a promising strategy to address the timing issue and improve treatment use in PSD, which is characterized by both over- and undertreatment ( 12 , 13 ). Moreover, meta-analytic evidence demonstrated that psychosocial interventions and pharmacotherapy are efficacious for prevention of depression after stroke, albeit with an increased risk of nausea and bone fracture for pharmacotherapy ( 14 , 15 ). Hence, preventive interventions should be applied only in groups at high risk of PSD in order to save resources and avoid the occurrence of adverse medication effects in people with low risk.…”
Section: Introductionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) are frequently selected for the treatment of PSD. It is worth noting that SSRIs are first-choice drugs (Mortensen and Andersen, 2015 ), but many patients experience many adverse events with the treatment, such as the risk of bone fractures and nausea (Richter et al, 2021 ). Psychotherapy is commonly used in the treatment of PSD patients.…”
Section: Introductionmentioning
confidence: 99%